Characteristics Of Acute Otitis Media Patients - Asyifah Andari Syarif; Hasma Idris Nohong; Husni Esa Darussalam (Sean Institute, 2024)
Otitis media (OM) is an inflammatory process that occurs in part or all of the middle ear mucosa, eustachian tube, mastoid antrum, and mastoid cells. OM is divided into Acute Otitis Media (OMA) and Otitis Media Effusion (OME). Acute Otitis Media (AOM) is an inflammation of the middle ear caused by blockage of the Eustachian tube, immune system disorders, and recurrent upper respiratory tract infections. Risk factors for acute otitis media are young age, orofacial abnormalities, exposure to cigarette smoke, short duration of breastfeeding, and family history of AOM. One of the main risk factors for acute otitis media is age. This literature review aims to determine the characteristics of patients with acute otitis media. The method used is literature review with Narrative Review design. The results obtained in this literature are that there are 7 articles obtained with restrictions from 2019 - 2024 and an in-depth analysis of the strengths and limitations of each article regarding the characteristics of patients with acute otitis media, 7 articles mention the characteristics of patients with acute otitis media. Acute otitis media in children is mostly caused by upper respiratory tract infections (URTIs), which are more commonly experienced by boys. This is due to boys who tend to be more active and cause a higher risk of exposure to ARI, and facilitate the occurrence of AOM.